UPAYA PENINGKATAN SADARI UNTUK DETEKSI DINI KANKER PAYUDARA PADA REMAJA PUTRI - Atika Kurnia Sari; Setianingsih (Stikes Yarsi Mataram, 2023)
Breast cancer is a disease that threatens women's health, but early detection through the Self-Examination method can increase the chances of recovery. Young women at SMK Cendikia Husada Kotabumi are a group that is susceptible to breast cancer, but awareness of the importance of self-awareness is still low among them. This community service aims to increase the awareness and skills of Sadari in young women at SMK Cendikia Husada Kotabumi to support early detection of breast cancer. The community engagement approach was conducted through socialization, education, and training on the Sadari method. The activity was carried out collaboratively between the community engagement team and the school, involving 27 adolescent girls as participants. The results of the activity showed a significant improvement in the level of knowledge and understanding of the adolescent girls regarding the importance of Sadari as an early detection method for breast cancer, as evidenced by the percentage results before and after the activity. Prior to the activity, the majority of the participants had a low level of knowledge, with 21 individuals (77.8%), while after the activity, the majority of the participants showed good knowledge, with 25 individuals (92.6%). They also successfully developed skills in performing Sadari independently. Community service through outreach, counseling, and training on Realization is effective in increasing awareness and skills of young women in early detection of breast cancer. These steps need to be continued and extended to other schools and communities to protect women's health more broadly